2020
DOI: 10.1177/1941738120916735
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Dysfunction and Mood in Collegiate Soccer Athletes

Abstract: Background: Sleep and mood are critical factors that contribute to health and wellness and are of particular interest to collegiate athletes who are juggling high physical, academic, and social demands. The aim of this study was to examine how psychological measures, player status, and sex-related factors were associated with perceived sleep quality. Hypothesis: Higher levels of global sleep dysfunction will be related to poor mood and increased anxiety, and there will be differences in sleep dysfunction in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…46 Acute physiological responses such as delayed onset of muscular soreness have been shown to contribute to poor sleep quality 3 while poor sleep quality is known to affect psychological factors such as “mood” or “stress”. 47…”
Section: Discussionmentioning
confidence: 99%
“…46 Acute physiological responses such as delayed onset of muscular soreness have been shown to contribute to poor sleep quality 3 while poor sleep quality is known to affect psychological factors such as “mood” or “stress”. 47…”
Section: Discussionmentioning
confidence: 99%
“…In literature, many studies have been conducted to identify changes in human mood status [14][15][16] and eating behaviors in different periods and conditions. However, there has not been any research on the impact of COVID-19 pandemic, which creates a scantiness/limitation that has never been seen in human life, on the emotional and emotional eating behaviors of young university students who are active athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a paradox exists in the sex-based sleep data. Despite the abundant evidence that women’s sleep patterns are objectively better than men’s, female athletes report a higher incidence of poor subjective sleep quality [ 13 15 ], and are 55% more likely to report sleep disturbances than male athletes [ 7 ]. Likewise, in two cross-sectional studies of athletes, female sex was found to be a significant predictor of poor subjective sleep quality [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that increases in mental strain and training load can be disruptive to athletes' sleep, through associations with reduced sleep duration, rapid eye movement (REM) sleep and sleep efficiency [4][5][6]. However, athletes' sleep quantity and quality are also influenced by their sex [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%